INTERNET GAMING-RELATED SUDDEN DEATH - AN AUTOPSY-BASED CASE REPORT (Journal of Forensic Medicine & Toxicology, 2022)
Competitive video gaming (i.e., electronic sports or esports), in which one competes against other human players, has rooted itself into today’s culture, especially amongst the younger demographic. Adolescents and young adults usually play for prolonged periods without taking any breaks. Among many modes of gaming, “Battle Royale” mode is an addictive one in which the participant is pitted against many other human players. We present a case in which a 16-year-old boy played a virtual reality first-person shooter game for a long duration and was found unresponsive at home. He was declared dead on arrival at our hospital. The postmortem examination revealed subarachnoid hemorrhage with intraventricular hemorrhage and pulmonary oedema. Histopathological examination of the brain had no evidence of aneurysms, arteriovenous malformation or inflammation. We highlight the unique role of stress-related subarachnoid hemorrhage, which has a grave prognosis by itself.
Keywords: Forensic pathology; Gaming disorder; Stress; Hypertension; Subarachnoid haemorrhage; Sudden death